The Psychometric Properties of the Norwegian version of The Lamer Social Competence in Preschool Scale (LSCIP) - ten Braak, Dieuwer; Lenes, Ragnhild; Backer-Grøndahl, Agathe (PsykTestBarn, 2023)
Description: The Lamer Social Competence in Preschool Scale (LSCIP) is a questionnaire-based measurement tool that has been developed to assess children's social competence in a Nordic preschool context. LSCIP consists of 31 items. The instrument builds upon the American measurement tool Social Skills Rating System (SSRS). The questionnaire can be answered by preschool personnel or parents. Responses are given on a five-point Likert scale ranging from one (very seldom) to five (very often) about how often the child has exhibited the competence in the past two months. Literature search: A systematic literature search for Norwegian, Danish, and Swedish studies reporting on the psychometric properties of LSCIP resulted in 109 hits. Five studies, including one master's thesis, were found through other sources. After full-text evaluation, a total of nine Norwegian studies were included. These studies provided documentation on both the instrument's reliability and validity. The age groups reported in the studies range from 1½ to 5½ years old. The samples are relatively large (ranging from n = 478 to n = 1426), but several of the studies report on subsamples from the same sample. There are no clinical samples in the included studies, and thus only the general population is reported on. Psychometrics: The results indicate good reliability for the entire scale, but somewhat less consistent reliability for the subscales. Construct validity is reported through two different approaches to the factor structure which provide somewhat conflicting results regarding whether LSCIP measures a multidimensional or unidimensional construct. There is a lack of documentation on convergent, discriminant, and criterion validity, and it is unknown how the instrument performs in clinical populations. There is, however, some documentation on concurrent and predictive validity. Conclusion: LSCIP is a relatively well-studied instrument in terms of some aspects of its psychometric properties. However, there are somewhat conflicting results regarding the subscales and lack of information on validity, norm data, and clinical subgroups. Therefore, we recommend that LSCIP be used only for research purposes for the time being.